Pengelolaan zakat produktif dalam mengentaskan permasalahan kemiskinan di Desa Junjung Kecamatan Sumbergempol Kabupaten Tulungagung - Sa'diyah, Halimatus (Maliki Interdisciplinary Journal, 2023)
Zakat is an act that has become an obligation, especially for Muslims, the command to tithe has been regulated in the Qur'an and Sunnah, assets that exceed daily basic needs should have been handed over to the amil to be managed and then handed over to the mustahiq, but in the process of managing and distributing zakat is still not optimal and does not fulfill the goals set forth in Law Number 23 of 2011, one of the goals of zakat is to create community welfare, especially for mustahiq, where to solve the above problems can be analyzed using the approach method qualitative which only refers to two data, namely primary through interviews and secondary through some literature which includes books, journals or articles, with the subject of making a management strategy or productive zakat management developed in Junjung Village, Sumbergempol District, Tulungagung Regency through the provision of capital to make as well as developing a business that has been determined in accordance with expertise in their respective fields.